2007
DOI: 10.2967/jnumed.106.038232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reconstruction Algorithms on Myocardial Blood Flow Measurement with 13N-Ammonia PET

Abstract: Filtered backprojection (FBP) is the traditional method for 13 N-NH 3 PET studies. Ordered-subsets expectation maximization (OSEM) is popular for PET studies because of better noise properties. Scant data exist on the effect of reconstruction algorithms on quantitative myocardial blood flow (MBF) estimation. Methods: Twenty patients underwent dynamic acquisition rest/stress 13 N-NH 3 studies. In Part 1, 19 rest/stress image pairs were reconstructed by FBP (10-mm Hanning filter) and by OSEM with 28 subsets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The partial volume effect (PVE) has been widely recognized as a factor affecting the accuracy of the ID-IF. 11 It has been shown that filtered back projection (FBP) and ordered subset expectation maximization (OS-EM) reconstruction techniques can also result in quantitative differences 12 but their effect is often neglected. In the present work, we investigated the effect of PVE correction methods and also the effect of image reconstruction algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The partial volume effect (PVE) has been widely recognized as a factor affecting the accuracy of the ID-IF. 11 It has been shown that filtered back projection (FBP) and ordered subset expectation maximization (OS-EM) reconstruction techniques can also result in quantitative differences 12 but their effect is often neglected. In the present work, we investigated the effect of PVE correction methods and also the effect of image reconstruction algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…A decade ago, when first-generation iterative techniques were introduced to clinical practice, some investigators found that the results were not interchangeable when compared to FBP. 8 It has been demonstrated that iterative technique such as OSEM do not provide accurate image-derived input functions for cardiac PET studies because of bias in count estimation, 9 although this bias can be potentially compensated by smoothing.…”
Section: Why Iterative Reconstruction Methods?mentioning
confidence: 99%
“…On the other hand, new reconstruction methods offer great potential for improved noise statistics 8 and improved image fidelity. 10 It has been demonstrated for cardiac dynamic applications that iterative techniques also yield improved image accuracy and less noise compared with FBP.…”
Section: Why Iterative Reconstruction Methods?mentioning
confidence: 99%
“…A recent analysis for N-13 ammonia flow studies found that image reconstruction type (ie, filtered backprojection or iterative) can significantly affect blood flow estimates, and smoothing filters after image reconstruction cause underestimation of absolute blood flow [31]. It is reasonable to assume that Rb-82 flow estimates will be influenced similarly by image reconstruction type and smoothing filter; however, this has not yet been studied.…”
Section: Quantifying Myocardial Blood Flow With Rb-82mentioning
confidence: 94%